Graphite negative electrode material and preparation method and application thereof

By optimizing the microcrystalline structure of graphite negative electrode material, ensuring the stability and safety of lithium-ion batteries during the cycle process, the problem of insufficient stability of graphite negative electrode material in the prior art is solved, and a longer cycle life and lower cycle life are achieved safety failure risk.

CN119218987APending Publication Date: 2024-12-31HUAWEI TECH CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202310802845.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing graphite negative electrode materials are insufficient in the circulation process, resulting in short cycle life of lithium-ion batteries, mainly due to capacity attenuation and safety failures caused by the growth of SEI film on the surface of graphite negative electrode and the deposition of lithium metal.

Method used

Provide a graphite negative electrode material, with large graphite crystal crystal size, moderate layer spacing and small number of crystal crystals. By optimizing the structure of graphite particles, it ensures the expansion uniformity of lithium ions when embedded, and reduces the rupture and regeneration and repair of SEI films. Impact of battery performance.

Benefits of technology

It improves the dynamic performance and long cycle stability of graphite negative electrode materials during the cycle process, reduces the risk of lithium excretion and safety failure risks such as battery capacity diving and thermal runaway, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119218987A_ABST
    Figure CN119218987A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of battery materials, in particular to a graphite negative electrode material and a preparation method and application thereof. The graphite negative electrode material comprises graphite particles, the average length La of the graphite particles in the alpha-axis direction of microcrystals is larger than or equal to 40 nm, the average thickness Lc of the graphite particles in the c-axis direction of the microcrystals is larger than or equal to 25 nm, and the interlayer spacing d002 ranges from 0.336 nm to 0.338 nm, and the number parameter of the microcrystals contained in each single graphite particle is defined as N = D503 / (La2 * Lc); d50 is the median particle size of the graphite particles, the unit is [mu] m, and the numerical value of N is more than 0 and less than or equal to 0.04. The graphite negative electrode material disclosed by the embodiment of the invention comprises the graphite particles with stable microcrystalline structure, large microcrystalline size and large interlayer spacing, so that the expansion and stress distribution uniformity of the negative electrode material in the circulation process is improved, the diffusion of ions in the graphite particles is facilitated, the consumption of active lithium is reduced, and the service life of the negative electrode material is prolonged. And the dynamic and super-long cycle stability of the graphite negative electrode material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of battery materials, and in particular relates to a graphite negative electrode material and a preparation method and application thereof. Background Art

[0002] In energy storage systems, lithium-ion batteries are the most mainstream energy storage carrier. In order to meet the needs of long life and low cost for large-scale energy storage systems, the cycle / storage characteristics of lithium batteries have become core competitiveness. At present, in the lithium iron phosphate-graphite battery system widely used in energy storage scenarios, the positive electrode lithium iron phosphate can maintain structural stability in the charge and discharge voltage range due to the high PO bond energy of the polyanion, and almost no active material loss occurs. Therefore, the shortcoming of the cycle life of the lithium iron phosphate-graphite battery system is mainly attributed to the negative electrode graphite. During the charge and discharge process of the ion battery, the battery negative electrode is polarized, and the electrolyte solution components undergo reduction and decomposition on the negative electrode surface to form new chemical products, which are deposited on the negative electrode surface to form a dense passivation film called "solid electrolyte interface", referred to as SEI film. The growth of SEI film on the surface of graphite negative electrode or lithium metal deposition will cause capacity decay or even diving. The growth of SEI film on the surface of graphite negative electrode comes from the expansion and contraction of the volume of graphite negative electrode during the process of lithium insertion and extraction, resulting in the formation of a newly exposed surface, which will react with the electrolyte and consume active lithium at the same time. The structural stability of graphite anode during the cycle process is one of the key factors affecting the cycle life of lithium-ion batteries.

[0003] Therefore, reducing the volume shrinkage and expansion of the graphite negative electrode during the cycle and improving the structural stability of the graphite negative electrode during the cycle are key factors in achieving long-term cycling of graphite negative electrode materials and lithium-ion batteries. Summary of the invention

[0004] The purpose of the present application is to provide a graphite negative electrode material and a preparation method and application thereof, aiming to solve the problem that the stability of existing graphite negative electrode materials during the cycle process needs to be improved.

[0005] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:

[0006] The first aspect of the present application provides a graphite negative electrode material, wherein the graphite negative electrode material comprises graphite particles having an average length La ≥ 40 nm along the a-axis direction of the microcrystal, an average thickness Lc ≥ 25 nm along the c-axis direction of the microcrystal, and an interlayer spacing d002 of 0.336 to 0.338 nm, and the number parameter of the microcrystals contained in a single graphite particle is defined as N = D50 3 / (La 2*Lc); wherein D50 is the median particle size of the graphite particles, in μm, and the numerical value of the crystallite number parameter N satisfies 0<N≤0.04.

[0007] The graphite negative electrode material provided in this application includes the following advantages:

[0008] On the one hand, the graphite crystallite size La in the graphite particles of the graphite negative electrode material is ≥40nm, Lc ≥25nm, and the number parameter of the crystallites contained in a single graphite particle is defined as N=D50 3 / (La 2 *Lc), wherein D50 is the median particle size of the graphite particles, in μm, and the numerical value of N satisfies 0<N≤0.04. Therefore, it is ensured that the graphite crystallites in the graphite particles of the graphite negative electrode material have a larger size. When lithium ions and other ions are embedded in the hexagonal mesh layer of the graphite crystallites, the large-sized graphite crystallites provide more deintercalation sites for the insertion and extraction of ions, which is more conducive to the ions entering between the sheets of graphite crystals from the edge embedding sites, improving the ion deintercalation efficiency, and facilitating the rapid transmission of ions. In addition, the kinetic performance of the graphite negative electrode material in the process of cyclic charge and discharge is improved, and the electrochemical properties of the applied battery, such as the rate performance and cycle performance, are improved. Thereby reducing the risk of lithium precipitation, and reducing the risk of safety failures such as battery capacity diving and thermal runaway.

[0009] On the other hand, the interlayer spacing d002 of graphite crystallites along the c-axis direction in the graphite particles of graphite negative electrode materials is 0.336-0.338nm, and the graphite interlayer spacing is large, which reduces the degree of graphitization. When lithium ions are embedded in the hexagonal mesh layer of graphite crystals, the interlayer spacing d(002) of the edge embedding site (002 crystal plane) is large, and the crystallite size Lc in the c-axis direction and the crystallite size La of the 110 crystal plane are large, which ensures the uniformity of expansion between crystallites when ions are embedded inside graphite particles. The expansion and stress distribution uniformity of graphite negative electrode materials during the cycle process are improved, so that the volume expansion and contraction of graphite negative electrode materials during the process of lithium insertion and extraction are small and uniform, and the graphite negative electrode materials have better kinetics and long cycle stability, and reduce the consumption rate of active lithium. Thereby reducing the impact of continuous rupture and regeneration and repair of SEI film on the surface of graphite negative electrode on battery cycle life and safety performance.

[0010] As some possible implementations of the graphite negative electrode material of the present application, the crystallite number parameter 0<N≤0.02. In some implementations, the crystallite number parameter 0.001≤N≤0.01. In this case, the graphite negative electrode material has better kinetics, reduces the risk of lithium plating, and reduces the risk of safety failures such as battery capacity diving and thermal runaway.

[0011] As some possible implementations of the graphite negative electrode material of the present application, the La is ≤ 200nm and the Lc is ≤ 200nm. In this case, the uniformity of expansion between crystallites when ions are embedded in the graphite particles is ensured, the long-cycle stability of the graphite negative electrode is improved, and the influence of continuous rupture and regeneration and repair of the SEI film on the surface of the graphite negative electrode on the battery cycle life and safety performance is reduced.

[0012] As some possible implementations of the graphite negative electrode material of the present application, the median particle size D50 of the graphite particles is 5 to 25 μm. In some implementations, the median particle size D50 of the graphite particles is 7 to 14 μm. In this case, the median particle size D50 of the graphite particles ensures the electrochemical comprehensive performance of the graphite negative electrode material, such as cycle stability and rate performance.

[0013] As some possible implementations of the graphite negative electrode material of the present application, the median particle size D50 of the graphite particles satisfies (D90-D10) / D50≤1.7 with the particle size D10 and the particle size D90. In some implementations, the median particle size D50 of the graphite particles satisfies (D90-D10) / D50≤1.5 with the particle size D10 and the particle size D90. In this case, the ratio of (D90-D10) / D50 is relatively small, indicating that the particle size distribution uniformity of the graphite particles is relatively high, which is beneficial to improve the flatness and thickness uniformity of the film layer prepared by the graphite negative electrode material.

[0014] As some possible implementations of the graphite negative electrode material of the present application, the specific surface area of ​​the graphite negative electrode material is 0.8 to 2.0 m 2 In some implementations, the specific surface area of ​​the graphite negative electrode material is 0.9 to 1.5 m 2 / g. In this case, the size range of the specific surface area of ​​the graphite negative electrode material balances the relationship between the reaction rate, capacity and mechanical stability of the graphite negative electrode material to achieve the best electrochemical performance and safety performance.

[0015] As some possible implementation methods of the graphite negative electrode material of the present application, the graphite particles are single particles or secondary particles. In actual application, single particle or secondary particle structure graphite negative electrode materials can be selected according to specific application requirements to ensure that the graphite negative electrode has the best electrochemical performance.

[0016] The second aspect of the present application provides a method for preparing a graphite negative electrode material, comprising the following steps:

[0017] forming a carbon precursor material into precursor particles;

[0018] After the precursor particles are graphitized, the graphite particles are screened to obtain a graphite negative electrode material; in the graphite particles, the average length La along the a-axis direction of the microcrystal is ≥40nm, the average thickness Lc along the c-axis direction of the microcrystal is ≥25nm, the interlayer spacing d002 is 0.336-0.338nm, and the number parameter of microcrystals contained in a single graphite particle is defined as N=D50 3 / (La 2 *Lc); wherein D50 is the median particle size of the graphite particles, in μm, and the numerical value of the crystallite number parameter N satisfies 0<N≤0.04.

[0019] The preparation method of the graphite negative electrode material provided in the present application is to prepare the carbon precursor material into precursor particles, perform graphitization treatment, and screen the graphite particles whose microcrystalline parameters meet the requirements, so as to obtain the graphite negative electrode material. The preparation process is simple and suitable for industrial large-scale production and application. And by screening the structure of the carbon source precursor material and regulating the graphitization process of the carbon precursor material, the microcrystalline structure of the graphite particles can be improved / optimized, the stability of the particle hierarchy and microcrystalline hierarchical structure of the graphite particles can be improved, and the rapid transmission of ions can be facilitated. In the prepared graphite negative electrode material, the number of graphite crystallites in the graphite particles is small, the relative size of the microcrystalline particles is large, and the graphite interlayer spacing is large, which reduces the degree of graphitization. When lithium ions are embedded in the hexagonal mesh layer of graphite crystals, the interlayer spacing d(002) of the edge embedding site (002 crystal plane) is large, the crystallite size Lc in the c-axis direction and the crystallite size La of the 110 crystal plane are large, so that when ions are embedded inside the graphite particles, they not only have better dynamics, improve the efficiency of ion extraction, facilitate the rapid transmission of ions, and improve the rate performance of the applied battery. In addition, there is a more uniform expansion performance between the crystallites, which improves the uniformity of expansion and stress distribution of the graphite negative electrode material during the cycle, reduces the consumption rate of active lithium, and improves the long-cycle stability and safety of the graphite negative electrode material.

[0020] As some possible implementations of the method for preparing the graphite negative electrode material of the present application, the fixed carbon content in the carbon precursor material is not less than 60%. In this case, a high fixed carbon content in the carbon precursor material means that the carbon content in the material is high, which is conducive to the preparation of high-performance graphite negative electrode materials.

[0021] As some possible implementations of the method for preparing the graphite negative electrode material of the present application, the carbon precursor material includes at least one of calcined petroleum coke, calcined petroleum coke, coal tar coke, and anthracite. In this case, these carbon precursor materials all have a high fixed carbon content, and the carbon structure in these carbon precursor materials is conducive to obtaining large-sized microcrystalline particles and graphite particles with large interlayer spacing after subsequent graphitization.

[0022] As some possible implementations of the method for preparing the graphite negative electrode material of the present application, the step of preparing the precursor particles includes: crushing the carbon precursor material into a particle sample with an average particle size D50 of 1 to 20 μm, and then performing a shaping process to obtain the precursor particles with an average particle size D50 of 1 to 30 μm. In this case, after the carbon precursor material is crushed, the particle sample obtained by crushing is then shaped to remove the particle edges and corners and improve the particle sphericity, which is not only beneficial to improving the processing performance of subsequent particles, but also helps to avoid problems such as too many edges and corners that are easy to break in subsequent application processes such as rolling.

[0023] As some possible implementations of the method for preparing the graphite negative electrode material of the present application, the step of preparing the precursor particles includes: after the carbon precursor material is made into particles by crushing and shaping, the particles are mixed with an organic carbon source for granulation, and the granulated product is carbonized to obtain the precursor particles. In this case, after the carbon precursor material is crushed and shaped into particles, it is mixed with an organic carbon source for granulation to obtain composite precursor particles, and then the composite precursor particles obtained by the mixed granulation are carbonized to convert the organic carbon source into carbon material by chemical reaction. At this time, the precursor particles obtained are secondary particles.

[0024] As some possible implementations of the method for preparing the graphite negative electrode material of the present application, the organic carbon source includes asphalt having a softening temperature of 100 to 500° C. In this case, the asphalt used is solid at room temperature, which is conducive to uniform mixing with the crushed precursor, and the crushed particles can be stably bonded together after the mixed granulation organic carbon source is softened to obtain a mixed granulation product.

[0025] As some possible implementations of the method for preparing the graphite negative electrode material of the present application, the average particle size D50 of the organic carbon source is 0.5 to 5 μm; in this case, the particle size of the organic carbon source is small, which is conducive to mixing and granulating with the crushed particles of the precursor to form composite particles.

[0026] As some possible implementations of the method for preparing the graphite negative electrode material of the present application, the mass ratio of the particles to the organic carbon source is 100:(0.5-5). In this case, it is not only conducive to the mixed granulation to form composite particles of the precursor and the organic carbon source, but also avoids the excessive proportion of the organic carbon source in the composite particles of the granulated product, resulting in excessive amorphous carbon content in the secondary precursor particles, which reduces the electrochemical performance of the subsequently prepared graphite negative electrode material.

[0027] As some possible implementations of the method for preparing the graphite negative electrode material of the present application, the carbonization treatment conditions include: in an inert atmosphere, heating to 600-900°C at a rate of 2-10°C / min and keeping warm for 1-10 hours. Under the carbonization conditions, in the secondary precursor particles obtained by mixing and granulating the precursor material and the organic carbon source, the organic carbon source undergoes a pyrolysis reaction at a high temperature, converting the carbon element in the organic carbon source into a structure that forms fixed carbon.

[0028] As some possible implementations of the graphite negative electrode material preparation method of the present application, the graphitization treatment conditions include: keeping the temperature at 2400-3000° C. for 24-72 hours. Under the graphitization treatment conditions, the precursor particles can be fully graphitized with high graphitization efficiency.

[0029] As some possible implementations of the method for preparing the graphite negative electrode material of the present application, the step of graphitization treatment includes: pre-carbonizing the precursor particles at a temperature of 700 to 1200°C for 2 to 7 days, and then keeping the temperature at a temperature of 2400 to 3000°C for 24 to 72 hours. In this case, the precursor particles are first pre-carbonized to remove the volatile matter in the precursor particles in advance, and then graphitized, which is conducive to the sample growing into more complete graphite crystals in the subsequent high-temperature graphitization.

[0030] As some possible implementations of the method for preparing the graphite negative electrode material of the present application, the step of screening the graphite particles includes: screening and demagnetizing the product after the graphitization treatment in sequence, and screening the graphite particles whose microcrystalline parameters meet the requirements. In this case, screening is used to remove larger particles and impurities, demagnetize, control magnetic foreign matter by electric current, further purify the product, and screen the microcrystalline parameters of the product to obtain the graphite particles whose microcrystalline parameters meet the requirements.

[0031] A third aspect of the present application provides a battery pole piece, wherein the battery pole piece contains the above-mentioned graphite negative electrode material or the graphite negative electrode material prepared by the above-mentioned method.

[0032] The battery pole piece provided by the present application contains the above-mentioned graphite negative electrode material, and the graphite negative electrode material has a stable microcrystalline structure. When applied to the battery pole piece, it can improve the expansion and stress distribution uniformity of the battery pole piece during the cycle process, reduce the consumption rate of active lithium, and thus achieve an ultra-long cycle of the battery system. In addition, the graphite negative electrode material has a large crystallite size and a large graphite layer spacing, which is conducive to the diffusion of lithium ions in the particles, improves the dynamics of the battery pole piece, and is conducive to the rapid charging of the battery.

[0033] A fourth aspect of the present application provides a secondary battery, wherein the secondary battery comprises the above-mentioned battery electrode.

[0034] The secondary battery provided in the present application includes the above-mentioned battery pole piece, which includes a graphite negative electrode material with a stable microcrystalline structure, a large microcrystalline size and a large graphite layer spacing, so that the battery pole piece has excellent kinetic performance and long-cycle stability, thereby improving the electrochemical properties of the secondary battery such as rate performance and cycle performance, reducing the risk of lithium plating, reducing the impact of continuous rupture and regeneration and repair of the SEI film on the electrode surface on the battery cycle life and safety performance, and reducing the risk of safety failures such as battery capacity diving and thermal runaway.

[0035] A fifth aspect of the present application provides an energy storage device, which includes the secondary battery mentioned above.

[0036] The energy storage device provided by the present application includes the secondary battery with the above-mentioned characteristics of good long-cycle stability, good rate performance, high safety performance, etc., which improves the comprehensive performance of the energy storage device such as stability and safety. Therefore, the energy storage device of the present application has good cycle performance and long service life.

[0037] A sixth aspect of the present application provides an electrical device, wherein the electrical device includes the secondary battery described above.

[0038] The electric device provided in the present application comprises a secondary battery having the above-mentioned characteristics of good long cycle stability, good rate performance, high safety performance, etc., thereby improving the use stability and safety of the electric device.

[0039] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 Schematic diagram of the structure of graphite microcrystals in the graphite negative electrode material provided in the embodiment of the present application, wherein (a) is a schematic diagram of the unit cell structure of graphite microcrystals, and (b) is a schematic diagram of the relationship between La, Lc, and d002 in the unit cell of graphite microcrystals;

[0041] Figure 2 It is a schematic diagram of the structure of natural graphite and coke-embedded artificial graphite provided by the prior art;

[0042] Figure 3 It is a schematic diagram of the structure of graphite particles and graphite crystallites in the graphite negative electrode material provided in the embodiment of the present application;

[0043] Figure 4 It is a schematic diagram of the process of preparing a graphite negative electrode material provided in an embodiment of the present application. DETAILED DESCRIPTION

[0044] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0045] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0046] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0047] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0048] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0049] The term "SEI" is the abbreviation of "Solid Electrolyte Interface", which means solid electrolyte interface membrane. During the charging and discharging process of ion batteries, the negative electrode of the battery is polarized, and the components of the electrolyte solution are reduced and decomposed on the surface of the negative electrode to form new chemical products, which are deposited on the surface of the negative electrode to form a dense passivation film. This passivation film is called solid electrolyte interface membrane, abbreviated as SEI membrane.

[0050] The term "LFP" is the abbreviation of "LiFePO4", which means "Lithium iron phosphate" in English. It means lithium iron phosphate, also known as lithium iron phosphate. It is a positive electrode material for lithium-ion batteries, also known as lithium iron phosphate batteries.

[0051] The term "La" is the length of the graphite crystal along the a-axis direction (sheet diameter direction). Figure 1 As shown. The C=C double bonds form a hexagonal structure, forming a plane, that is, a single graphite sheet; multiple sheets stacked on each other form a graphite crystal, and the radial direction of a single graphite sheet is the direction of the a-axis (corresponding to the 110 crystal plane). La represents the length of the a-axis direction in the graphite crystal.

[0052] The term "Lc" is the thickness of the graphite crystal stacked along the c-axis direction (the direction perpendicular to the layer structure). Figure 1 As shown. The C=C double bonds form a hexagonal structure, forming a plane, that is, a single graphite sheet; multiple sheets stacked on each other form a graphite crystal, and the direction perpendicular to the sheet structure is the c-axis direction (corresponding to the 002 crystal plane). Lc represents the stacking thickness along the c-axis direction in the graphite crystal.

[0053] The term "d002" is the distance between two adjacent sheets along the c-axis in a graphite crystal. Figure 1 As shown. The C=C double bonds form a hexagonal structure, forming a plane, that is, a single graphite sheet; multiple sheets stacked on each other form a graphite crystal. Along the c-axis direction perpendicular to the sheet structure, the spacing between adjacent graphite sheets is represented by d002. The ideal graphite crystal interlayer spacing is 0.3354nm (also expressed as ), the larger the interlayer spacing in the graphite crystal, the more the graphite tends to be amorphous carbon. The interlayer spacing of amorphous carbon is greater than or equal to 0.344nm and can be as high as 0.37nm (also expressed as ). Among them, the relationship between La, Lc, and d002 is as shown in the attached Figure 1 As shown in (b).

[0054] The term "D10" refers to the particle size corresponding to the cumulative particle size distribution number of a sample (the percentage of all particle sizes before or after itself) reaching 10%. Its physical meaning is that particles with a particle size smaller than it account for 10%.

[0055] The term "D50" refers to the particle size corresponding to when the cumulative particle size distribution percentage of a sample reaches 50%. Its physical meaning is that particles with a particle size larger than it account for 50%, and particles with a particle size smaller than it also account for 50%. D50 is also called the median diameter or median particle size. D50 is often used to indicate the average particle size of powders.

[0056] The term "D90" refers to the particle size corresponding to when the cumulative particle size distribution number of a sample reaches 90%. Its physical meaning is that 90% of the particles have a particle size smaller than it.

[0057] The term "battery cell" refers to a single electrochemical cell containing positive and negative electrodes. It is the smallest unit of a power battery and also an energy storage unit. The components of a battery cell include three main parts: positive and negative electrode sheets, electrolyte, and diaphragm.

[0058] The term "module" means that when multiple battery cells are encapsulated together in the same outer shell frame and connected to the outside through a unified boundary, this forms a module.

[0059] The term "battery pack" refers to the combination of several modules that are controlled or managed together by the battery management system (BMS) and the thermal management system. The unified whole is called a battery pack.

[0060] At present, from the perspective of the development of the market situation, with the continuous expansion of the application field of power batteries, the market demand is also constantly expanding. In particular, lithium-ion batteries have been rapidly and widely popularized and applied in the fields of mobile terminals, energy storage devices, electric vehicles, etc. Therefore, higher and higher requirements are also put forward for the performance of lithium-ion batteries such as initial efficiency, energy density, and cycle life. Lithium-ion batteries contain electrolytes. During the charging and discharging process of ion batteries, the negative electrode of the battery is polarized, and the components of the electrolyte solution are reduced and decomposed on the surface of the negative electrode to form new chemical products, which are deposited on the surface of the negative electrode to form a dense passivation film. This passivation film is called a solid electrolyte interface film, or SEI film for short.

[0061] Although the formation of the SEI film improves the cycle performance and service life of the electrode, some lithium ions will be consumed during the formation of the SEI film, resulting in an increase in the irreversible capacity of the electrode material and a reduction in the initial coulombic efficiency of the electrode material. In addition, during the subsequent charging and discharging process of the battery, the graphite negative electrode will expand and shrink in volume due to the deintercalation of lithium, resulting in the formation of a newly exposed surface, which will react with the electrolyte and consume active lithium again. Therefore, during the charging and discharging process of the battery, the SEI film on the surface of the graphite negative electrode will continue to repair and grow, and during the repair and growth process, the lithium ions in the ion battery will continue to be consumed, thereby reducing the cycle performance of the battery.

[0062] The graphite crystals in the graphite negative electrode are in a lamellar structure. Figure 1 As shown, carbon atoms form covalent bonds with sp2 hybridization, and are connected by C=C double bonds in the same plane to form a hexagonal ring extension, forming a plane layer (ink flake surface), as shown in the attached Figure 1 In (a), there are layers A, B, etc. The layers are stacked together through weak van der Waals forces and π-π delocalized orbital interactions to form graphite crystals. The radial direction of a single layer is the direction of the a axis (corresponding to the 110 crystal plane), and the direction perpendicular to the layer structure is the c axis (corresponding to the 002 crystal plane). The distance between adjacent layers in an ideal graphite crystal is 0.3354nm (also expressed as ), while the distance between adjacent sheets in amorphous graphite is as high as 0.37nm (also expressed as ). During the lithium ion embedding process, the graphite crystal gradually transitions from the original carbon structure to the fully lithiated LiC6 structure, and enters the graphite crystal sheets in stages according to the amount of lithium ion embedding, accompanied by the interlayer spacing in the c-axis direction from the original become When lithium is removed, it shrinks in the opposite direction. Therefore, the volume change of the graphite negative electrode during the process of lithium ion insertion and extraction comes from the expansion and contraction of the graphite crystal in the c-axis direction. In micron-sized graphite particles, the expansion of lithium extraction at the particle level is not only related to the initial interlayer spacing (d002) of the graphite crystal and its own expansion, but also to the orientation degree, size and bonding mode of the graphite crystal in the graphite particles. Therefore, factors that are not conducive to the structural stability of the graphite negative electrode will aggravate the volume change of the graphite negative electrode during the cycle process, thereby leading to the loss of overall active lithium in the lithium-ion battery and a reduction in the battery cycle life.

[0063] Therefore, in order to improve the cycle life of ion batteries, it is necessary to improve the structural stability of graphite negative electrode materials during the cycle process. Figure 2 As shown, the composite of natural graphite and coke-based artificial graphite, natural graphite and coke-based artificial graphite are used together as negative electrode materials. Although the conductivity characteristics of natural graphite can be improved to a certain extent, it is still unable to effectively solve the inherent characteristics of natural graphite such as multiple pores inside and large specific surface area, resulting in large expansion during the cycle, fast loss of active lithium, and obvious disadvantages in the cycle. In addition, coke-based artificial graphite has a small Lc, a small d002 interlayer spacing, and a large expansion after lithium insertion, which improves the effect of the cycle. In other known schemes, small graphite particles are bonded into spherical secondary particles by additives to increase the sphericity of graphite. Although it is beneficial to improve the tap density and compaction density of graphite negative electrode materials, the expansion characteristics of the original particles of graphite negative electrode materials themselves have not changed, and the stress accumulation caused by long-term circulation will cause the bonding joint to break, resulting in loss of active substances and increase of side reaction area, thereby accelerating battery decay.

[0064] Based on the above considerations, in order to solve the problem of long cycle life of ion batteries, after in-depth research, a graphite negative electrode material is proposed. The graphite particles contained in the graphite negative electrode material have larger crystallite sizes La and Lc, and the interlayer spacing d002 along the c-axis direction is also larger. The parameter of the number of crystallites contained in a single graphite particle is defined as N = D50 3 / (La 2*Lc), by limiting the parameters of graphite particle size D50 and crystallite size La and Lc, the number of crystallites contained in the graphite particles is small, so that the size of graphite crystallites contained in the graphite particles is larger. At this time, when lithium ions are embedded in the hexagonal mesh layer of the graphite crystal, the interlayer spacing d(002) of the edge embedding site (002 crystal plane) is large, the crystallite size Lc in the c-axis direction and the crystallite size La of the 110 crystal plane are large, ensuring the uniformity of expansion between crystallites when ions are embedded in the graphite particles. As a result, the volume expansion and contraction of the graphite negative electrode material during the process of lithium extraction is small and uniform, and the graphite negative electrode material has better kinetics and long cycle stability. Reduce the impact of the continuous repair and regeneration of the SEI film on the surface of the graphite negative electrode due to rupture on the battery cycle life and safety performance.

[0065] For the convenience of description, the following embodiments of the present application are described by taking graphite negative electrode materials and preparation methods and applications thereof as examples.

[0066] In a first aspect, an embodiment of the present application provides a graphite negative electrode material, wherein the graphite negative electrode material includes graphite particles having an average length La ≥ 40 nm along the a-axis direction of the microcrystal, an average thickness Lc ≥ 25 nm along the c-axis direction of the microcrystal, and an interlayer spacing d002 of 0.336 to 0.338 nm, and the number parameter of microcrystals contained in a single graphite particle is defined as N = D50 3 / (La 2 *Lc); wherein D50 is the median particle size of the graphite particles, in μm, and the value of the crystallite number parameter N satisfies 0<N≤0.04.

[0067] Thus, the graphite negative electrode material provided in the embodiment of the present application has the following advantages:

[0068] On the one hand, the graphite crystallite size La ≥ 40nm, Lc ≥ 25nm in the graphite particles of the graphite negative electrode material, and the number parameter of crystallites contained in a single graphite particle is defined as N = D50 3 / (La 2 *Lc), where D50 is the median particle size of the graphite particles, in μm, and the value of N satisfies 0<N≤0.04. Therefore, it is ensured that the graphite crystallites in the graphite particles of the graphite negative electrode material have a larger size. When lithium ions are embedded in the hexagonal mesh layer of the graphite crystallites, the large-sized graphite crystallites provide more deintercalation sites for the insertion and extraction of ions, which is more conducive to the ions entering between the sheets of graphite crystals from the edge embedding sites, improving the ion deintercalation efficiency, and facilitating the rapid transmission of ions. This improves the kinetic performance of the graphite negative electrode material during the cyclic charge and discharge process, and improves the electrochemical properties of the applied battery, such as the rate performance and cycle performance. This reduces the risk of lithium plating, and reduces the risk of safety failures such as battery capacity diving and thermal runaway.

[0069] On the other hand, the interlayer spacing d002 of graphite crystallites along the c-axis direction in the graphite particles of graphite negative electrode materials is 0.336-0.338nm, and the graphite interlayer spacing is large, which reduces the degree of graphitization. When lithium ions are embedded in the hexagonal mesh layer of graphite crystals, the interlayer spacing d(002) of the edge embedding site (002 crystal plane) is large, and the crystallite size Lc in the c-axis direction and the crystallite size La of the 110 crystal plane are large, which ensures the uniformity of expansion between crystallites when ions are embedded inside graphite particles. The expansion and stress distribution uniformity of graphite negative electrode materials during the cycle process are improved, so that the volume expansion and contraction of graphite negative electrode materials during the process of lithium insertion and extraction are small and uniform, and the graphite negative electrode materials have better kinetics and long cycle stability, and reduce the consumption rate of active lithium. Thereby reducing the impact of continuous rupture and regeneration and repair of SEI film on the surface of graphite negative electrode on battery cycle life and safety performance.

[0070] In some possible embodiments, in the graphite negative electrode material, the parameter N of the number of crystallites in a single graphite particle is D50 3 / (La 2 *Lc), where the unit of D50 is μm, and the units of Lc and La are nm, so the unit of the crystallite number parameter can be expressed as μm / nm. In the calculation formula of the crystallite number parameter of the embodiment of the present application, when the units of D50, Lc and La are determined, the value of N is only related to the numerical value and is no longer affected by the parameter unit. The crystallite number parameter N represents the graphite crystallite number parameter contained in a single graphite particle. The numerical value of N satisfies 0<N≤0.04, which is the average value, indicating that the number of graphite crystallites in a single graphite particle is not higher than 0.04*10 9 For example, 0<N≤0.039, 0<N≤0.038, 0<N≤0.037, 0<N≤0.035, 0<N≤0.033, 0<N≤0.031, 0<N≤0.03, 0<N≤0.028, 0<N≤0.026, 0<N≤0.025, 0<N≤0.023, 0<N≤0.021, 0<N≤0.02, 0<N≤0.01 8. 0<N≤0.016, 0<N≤0.015, 0<N≤0.014, 0<N≤0.012, 0<N≤0.01, 0<N≤0.009, 0<N≤0.008, 0<N≤0.007, 0<N≤0.006, 0<N≤0.005, 0<N≤0.004, 0<N≤0.003, 0<N≤0.002, 0<N≤0.001, etc.

[0071] In some specific embodiments, the graphite particles are approximated into a cube, whose edge length is D50, and the volume of the graphite particles is expressed as D50. 3 The structural diagram of graphite particles and graphite microcrystals is shown in the attached figure. Figure 3 As shown, the microcrystalline particles are approximated as cuboids. The size of a single graphite sheet is the size of the bottom area of ​​the microcrystalline particles, expressed as La*La. The height (thickness) of the microcrystalline particles is Lc. At this time, the volume of the microcrystalline particles is expressed as La 2 *Lc. Therefore, the number of crystallites contained in a single graphite particle can be calculated by the ratio of the volume of the graphite particle to the volume of the crystallite particle. The crystallite number parameter is approximately expressed as N = D50 3 / (La 2 *Lc). Since graphite particles and microcrystalline particles are not necessarily regular polyhedrons, the number of microcrystalline represents an approximate average parameter rather than an exact quantitative value.

[0072] In some specific embodiments, in the graphite negative electrode material, the parameter of the number of crystallites in a single graphite particle is 0<N≤0.03. In a further embodiment, the parameter of the number of crystallites is 0<N≤0.02. In a further embodiment, the parameter of the number of crystallites is 0.001≤N≤0.01. The above embodiments of the present application further limit the parameter of the number of crystallites in the graphite particles to ensure that the graphite crystallites in the graphite particles have a larger size. The large-sized graphite crystallites provide more deintercalation sites for the insertion and extraction of ions, which is more conducive to the ions entering between the sheets of graphite crystals from the edge embedding sites, improving the efficiency of ion deintercalation, and facilitating the rapid transmission of ions. Thereby, the graphite negative electrode material has better kinetics, reduces the risk of lithium precipitation, and reduces the risk of safety failures such as battery capacity diving and thermal runaway.

[0073] Exemplarily, the parameter N of the number of crystallites in a single graphite particle can be typically but not limited to 0.0205, 0.0039, 0.0088, 0.0391, 0.04, 0.037, 0.035, 0.033, 0.03, 0.028, 0.025, 0.023, 0.02, 0.018, 0.015, 0.013, 0.01, 0.009, 0.006, 0.005, 0.003, 0.001, etc.

[0074] In some possible embodiments, the value range of the interlayer spacing d002 of graphite crystallites along the c-axis direction in the graphite particles of the graphite negative electrode material is typically but not limited to 0.336-0.338 nm, 0.336-0.3363 nm, 0.3363-0.3364 nm, 0.3364-0.3368 nm, 0.3368-0.337 nm, 0.337-0.3373 nm, 0.3373-0.3375 nm, 0.3375-0.3378 nm, 0.3378-0.338 nm, etc. In this case, the interlayer spacing of the graphite crystallites along the c-axis direction is large, which reduces the degree of graphitization, is more conducive to the embedding of lithium ions and the like into the hexagonal mesh layer of the graphite crystal, and improves the expansion uniformity between the crystallites when the ions are embedded in the graphite particles, thereby improving the kinetics and long cycle stability of the graphite negative electrode material.

[0075] In some possible embodiments, the graphite crystallite parameters in the graphite particles have an average length La≥40nm and La≤200nm along the crystallite a-axis direction, and an average thickness Lc≥25nm and Lc≤200nm along the crystallite c-axis direction. In this case, the crystallite size La of the graphite crystallite in the 110 crystal plane in the graphite particles is relatively large, and the crystallite thickness Lc in the c-axis direction is also relatively large, thereby ensuring that the graphite crystallite has a relatively large size, and when lithium ions are embedded in the hexagonal mesh layer of the graphite crystal, the expansion uniformity between the crystallites when the ions are embedded in the graphite particles is ensured, the long cycle stability of the graphite negative electrode is improved, and the influence of the continuous rupture and regeneration and repair of the SEI film on the surface of the graphite negative electrode on the battery cycle life and safety performance is reduced.

[0076] Exemplarily, the average length La of the graphite crystallite parameter along the crystallite a-axis direction in the graphite particles may be typically but not limited to 40 to 200 nm, 50 to 200 nm, 60 to 200 nm, 70 to 200 nm, 80 to 200 nm, 90 to 200 nm, 100 to 200 nm, 110 to 200 nm, 120 to 200 nm, 130 to 200 nm, 140 to 200 nm, 150 to 200 nm, 160 to 200 nm, 170 to 200 nm, 180 to 200 nm, 190 to 200 nm, 200 to 200 nm, 210 to 200 nm, 220 to 200 nm, 230 to 200 nm, 240 to 200 nm, 250 to 200 nm, 260 to 200 nm, 270 to 200 nm, 280 to 200 nm, 290 to 200 nm, 300 to 200 nm, 310 to 200 nm, 320 to 200 nm, 330 to 200 nm, 340 to 200 nm, 360 to 200 nm, 370 to 200 nm, 380 to 200 nm, 390 to 200 nm, 400 to 200 nm, 410 to 200 nm, 420 to 200 nm, 430 to 200 nm, 440 to 200 nm, 450 to 200 nm, 460 to 200 nm, 470 to 200 nm, 480 to 50~200nm, 160~200nm, 170~200nm, 180~200nm, 190~200nm, 50~190nm, 60~180nm, 70~170nm, 80~160nm, 90~150nm, 100~140nm, 110~130nm, 42.5~51nm, 51~55nm, 55~58nm, 58~60.5nm, etc.

[0077] The average thickness Lc of the graphite crystallite parameter along the crystallite c-axis direction in the exemplary graphite particles may be typically but not limited to 25 to 200 nm, 30 to 200 nm, 40 to 200 nm, 50 to 200 nm, 60 to 200 nm, 70 to 200 nm, 80 to 200 nm, 90 to 200 nm, 100 to 200 nm, 110 to 200 nm, 120 to 200 nm, 130 to 200 nm, 140 to 200 nm, 150 to 200 nm, 160 to 200 nm, 170 to 200 nm, 180 to 200 nm, 190 to 200 nm, 200 to 200 nm, 210 to 200 nm, 220 to 200 nm, 230 to 200 nm, 240 to 200 nm, 250 to 200 nm, 260 to 200 nm, 270 to 200 nm, 280 to 200 nm, 290 to 200 nm, 300 to 200 nm, 310 to 200 nm, 320 to 200 nm, 330 to 200 nm, 340 to 200 nm, 360 to 200 nm, 370 to 200 nm, 380 to 200 nm, 390 to 200 nm, 400 to 200 nm, 410 to 200 nm, 420 to 200 nm, 430 to 200 nm, 440 to 200 nm, 450 to 200 nm, 460 to 200 nm, 0nm, 180~200nm, 190~200nm, 30~190nm, 40~180nm, 50~170nm, 60~160nm, 70~150nm, 80~140nm, 90~130nm, 100~120nm, 25~30nm, 30~35nm, 35~38nm, 38~40.1nm, 40.1~42.6nm, 42.6~45nm, 45~50nm, 50~60nm, 60~70nm, 70~80nm, 80~90nm, etc.

[0078] In some possible embodiments, the median particle size D50 of the graphite particles is 5 to 25 μm. In this case, the particle size represents the median value of the particle size distribution of the graphite particles. Among all graphite particle samples, 50% of the particles have a diameter greater than this value and 50% of the particles have a diameter less than this value. The median particle size D50 of the graphite particles ensures the electrochemical comprehensive properties such as cycle stability and rate performance of the graphite negative electrode material. Exemplarily, the median particle size D50 of the graphite particles can be typically but not limitatively 5 to 24 μm, 5 to 22 μm, 5 to 20 μm, 5 to 18 μm, 5 to 16 μm, 5 to 14 μm, 5 to 12 μm, 5 to 10 μm, 5 to 8 μm, 5 to 6 μm, 5 to 7 μm, 7 to 9 μm, 9 to 11 μm, 11 to 14 μm, 14 to 16 μm, 16 to 18 μm, etc.

[0079] In some possible embodiments, the median particle size D50 of the graphite particles is 7 to 14 μm. In the case of the median particle size of the graphite particles, the graphite particles with small particle size have a larger specific surface area, providing more active surface area for the insertion and extraction of ions, which is beneficial to improve the rate performance and cycle performance of the battery used for the graphite negative electrode material. Exemplarily, the median particle size D50 of the graphite particles can be 7 to 8.3 μm, 8.3 to 9 μm, 9 to 10 μm, 10 to 11 μm, 11 to 11.2 μm, 11.2 to 11.5 μm, 11.5 to 12 μm, 12 to 13 μm, 13 to 14 μm, etc.

[0080] In some possible embodiments, the median particle size D50 of the graphite particles satisfies (D90-D10) / D50≤1.7 with the particle size D10 and the particle size D90. In this case, D90 means that 90% of the particles in the graphite particle sample have a particle size smaller than the particle size D90, and D10 means that 10% of the particles in the graphite particle sample have a particle size smaller than the particle size D10. (D90-D10) / D50 represents the particle size distribution width of large and small particles after all the particles in the graphite particles are combined together. The smaller the value of (D90-D10) / D50, the more uniform the particle size in the graphite particles. In the embodiment of the present application, (D90-D10) / D50≤1.7, the ratio is relatively small, indicating that the uniformity of the particle size distribution of the graphite particles is relatively high, which is beneficial to improve the flatness and thickness uniformity of the film layer prepared from the graphite negative electrode material. If the particle size distribution of graphite particles is too wide, on the one hand, it will affect the relationship between graphite particles and microcrystals. On the other hand, excessive content of fine powder in the graphite negative electrode material will affect the cycle performance of the negative electrode material, thereby affecting the cycle performance of the battery cell.

[0081] Exemplarily, the (D90-D10) / D50 of the graphite particles can be typically but not limitatively (D90-D10) / D50≤1.7, (D90-D10) / D50≤1.6, (D90-D10) / D50≤1.5, (D90-D10) / D50≤1.4, (D90-D10) / D50≤1.3, (D90-D10) / D50≤1.2, (D90-D10) / D50≤1.1, etc.

[0082] In some possible embodiments, the median particle size D50 of the graphite particles satisfies (D90-D10) / D50≤1.5 with the particle size D10 and the particle size D90. In this case, the particle size distribution of the graphite particles has a higher uniformity, which is more conducive to improving the flatness and thickness uniformity of the negative electrode film layer prepared from the graphite negative electrode material, thereby improving the structure and cycle stability of the negative electrode.

[0083] In some possible embodiments, the specific surface area of ​​the graphite negative electrode material is 0.8 to 2.0 m 2 / g. In this case, the size of the specific surface area of ​​the graphite negative electrode material will affect its electrochemical performance. Specifically, a larger specific surface area generally means more active surfaces available for electrochemical reactions to occur, and thus the electrochemical reaction rate and capacity of the graphite negative electrode material can be improved. However, a larger specific surface area may also cause the mechanical stability of the graphite negative electrode material to decrease, making it prone to falling off and damage, thereby affecting its cycle life and safety performance, and being detrimental to processing performance. Therefore, the size range of the specific surface area of ​​the graphite negative electrode material in the embodiment of the present application balances the relationship between the reaction rate, capacity and mechanical stability of the graphite negative electrode material to achieve optimal electrochemical performance and safety performance.

[0084] For example, the specific surface area of ​​the graphite negative electrode material may be typically but not limited to 0.8 to 2.0 m 2 / g, 0.9~1.9m 2 / g, 1.0~1.8m 2 / g, 1.1~1.7m 2 / g, 1.2~1.6m 2 / g, 1.3~1.5m 2 / g, 0.8~1.8m 2 / g, 0.8~1.4m 2 / g, 0.8~1.2m 2 / g, 0.8~1.0m 2 / g, 1.0~2.0m 2 / g, 1.2~2.0m 2 / g, 1.4~2.0m 2 / g, 1.6~2.0m 2 / g, 1.8~2.0m 2 / g, etc.

[0085] In some possible embodiments, the specific surface area of ​​the graphite negative electrode material is 0.9 to 1.5 m 2 / g. In this case, the specific surface area of ​​the graphite negative electrode material can better take into account the reaction rate, capacity and mechanical stability of the graphite negative electrode material, so that the graphite negative electrode material has better electrochemical stability and safety performance.

[0086] In some possible embodiments, the graphite particles are single particles or secondary particles. The single graphite particles in the embodiment of the present application refer to the graphite particles obtained by directly graphitizing the graphite precursor material after it is crushed into a target size, that is, single particles. Secondary particles refer to the graphite precursor material after it is crushed into a target size, the precursor particles are mixed and granulated with an organic carbon source such as asphalt to obtain composite precursor particles, and then the composite precursor particles obtained by the mixed granulation are carbonized, pre-carbonized, graphitized, etc., and the graphitized product is crushed again to obtain graphite particles of the target size, which is obtained at this time as secondary particles. Compared with single-particle graphite negative electrode materials, secondary particle graphite negative electrode materials have better thermal conductivity, which is beneficial to reduce the temperature rise of the material and improve its safety performance. Secondary particle graphite negative electrode materials have higher specific surface area and more microporous structures, which are beneficial to improve their electrochemical reaction rate and capacity on the one hand, and on the other hand, high specific surface area and microporous structure may also cause structural changes and capacity decay in long-term use. In addition, the mechanical stability of secondary particle graphite negative electrode materials is not as good as that of single particle graphite negative electrode materials, and they are prone to falling off and damage, which affects their cycle life and safety performance. In addition, the preparation process of secondary particles is relatively complicated and the cost is relatively high. Therefore, in the actual application process, single particle or secondary particle graphite negative electrode materials can be selected according to specific application requirements to ensure that the graphite negative electrode has the best electrochemical performance.

[0087] The graphite negative electrode material provided in the embodiments of the present application can be prepared by the following embodiment method.

[0088] Second, as attached Figure 4 As shown, the present application embodiment provides a method for preparing a graphite negative electrode material, comprising the following steps:

[0089] S10. Forming a carbon precursor material into precursor particles;

[0090] S20. After the precursor particles are graphitized, the graphite particles are screened to obtain a graphite negative electrode material; in the graphite particles, the average length La along the a-axis direction of the microcrystal is ≥40nm, the average thickness Lc along the c-axis direction of the microcrystal is ≥25nm, the interlayer spacing d002 is 0.336-0.338nm, and the number parameter of microcrystals contained in a single graphite particle is defined as N=D50 3 / (La 2 *Lc); wherein D50 is the median particle size of the graphite particles, in μm, and the value of the crystallite number parameter N satisfies 0<N≤0.04.

[0091] The second aspect of the present application provides a method for preparing a graphite negative electrode material, wherein a carbon precursor material is made into precursor particles, graphitized, and graphite particles with crystallite parameters that meet the requirements are screened to obtain a graphite negative electrode material. In the prepared graphite negative electrode material, the crystallite parameters of the graphite particles meet the following requirements: the average length La along the crystallite a-axis direction is ≥40nm, the average thickness Lc along the crystallite c-axis direction is ≥25nm, the interlayer spacing d002 is 0.336-0.338nm, and the crystallite number parameter contained in a single graphite particle is defined as N=D50. 3 / (La 2 *Lc), where the unit of median particle size D50 is μm. It ensures that the number of graphite crystallites in the graphite particles is small, the relative size of the crystallite particles is large, and the graphite layer spacing is large, which reduces the degree of graphitization. When lithium ions are embedded in the hexagonal mesh layer of the graphite crystal, the layer spacing d(002) of the edge embedding site (002 crystal plane) is large, the crystallite size Lc in the c-axis direction and the crystallite size La of the 110 crystal plane are large, so that when ions are embedded inside the graphite particles, it not only has better dynamics, improves the efficiency of ion deintercalation, is conducive to the rapid transmission of ions, and improves the rate performance of the applied battery; and there is a more uniform expansion performance between the crystallites, which improves the expansion and stress distribution uniformity of the graphite negative electrode material during the cycle, reduces the active lithium consumption rate, and improves the long-cycle stability and safety of the graphite negative electrode material. In addition, the preparation process of the embodiment of the present application is simple and suitable for industrial large-scale production and application. In addition, by screening the structure of the carbon source precursor material and regulating the graphitization process of the carbon precursor material, the microstructure of the graphite particles can be improved / optimized, and the stability of the particle level and microcrystalline level structure of the graphite particles can be improved, which is beneficial to the rapid transmission of ions.

[0092] In the above step S10, the carbon precursor material is made into precursor particles; by crushing the carbon precursor material, the carbon precursor material is processed into particles with appropriate particle size and relatively uniform, which is beneficial to improving the efficiency of subsequent graphitization treatment.

[0093] In some possible embodiments, the fixed carbon content in the carbon precursor material is not less than 60%; in this case, the high fixed carbon content in the carbon precursor material means that the carbon element content in the material is relatively high, which is conducive to the preparation of high-performance graphite negative electrode materials. Specifically, carbon precursor materials with high fixed carbon content can withstand high temperature environments, are not easy to decompose and burn, and have good thermal stability. At the same time, it has high mechanical strength and can provide better tensile, bending and compression properties. And it is conducive to the preparation of graphite negative electrode materials with better electrical and thermal conductivity. Exemplarily, the fixed carbon content in the carbon precursor material can be typically but not limitatively ≥60%, further ≥70%, further ≥80%, further ≥90%, etc.

[0094] In some possible embodiments, the carbon precursor material includes at least one of calcined petroleum coke, calcined petroleum coke, coal tar coke, and anthracite. The carbon precursor materials used in the embodiments of the present application all have a high fixed carbon content, and the carbon structure in these carbon precursor materials is conducive to obtaining large-sized microcrystalline particles and graphite particles with large interlayer spacing after subsequent graphitization. Among them, calcined petroleum coke refers to the original petroleum coke obtained through the petroleum coking process without high temperature treatment. Its structure is relatively loose, contains a large amount of volatiles and impurities, and its fixed carbon content is below 80%. The physical and chemical properties of calcined petroleum coke are relatively stable. Calcined petroleum coke refers to the material obtained by calcining calcined petroleum coke at high temperature. Calcined petroleum coke has a higher fixed carbon content, a lower volatile content and better physical properties, such as mechanical strength, electrical conductivity and thermal conductivity. Coal tar coke refers to the material obtained by coking coal tar or asphalt raw materials. Its structure is denser than calcined petroleum coke, and its fixed carbon content and mechanical properties are higher. Anthracite is a type of coal with a high carbon content, which can reach more than 80%. Anthracite has a relatively dense structure and contains a small amount of oxygen, hydrogen and other elements, but its ash content is high, and it has good combustion performance and chemical stability.

[0095] In some possible embodiments, the step of preparing precursor particles includes: crushing the carbon precursor material into a particle sample with an average particle size D50 of 1 to 20 μm, and then performing a shaping process to obtain precursor particles with an average particle size D50 of 1 to 30 μm. The embodiment of the present application crushes the carbon precursor material into a particle sample with an average particle size D50 of 1 to 20 μm by mechanical grinding, roller grinding or air flow grinding, and then performs a shaping process on the crushed particle sample to remove the particle edges and corners and improve the sphericity of the particles, which is not only beneficial to improving the processing performance of subsequent particles, but also beneficial to avoiding problems such as too many edges and corners that are easy to break in subsequent application processes such as rolling. In the crushing and shaping process, air induced fine powder is used to remove the broken fine powder and angular fine powder, reduce the number of fine particles, and obtain precursor particles with an average particle size D50 of 1 to 30 μm. This particle size is conducive to the subsequent uniform graphitization treatment to obtain a graphite negative electrode material of suitable particle size.

[0096] Exemplarily, the average particle size D50 of the precursor particles can typically but not limitatively be 1-30 μm, 2-29 μm, 3-28 μm, 4-27 μm, 5-26 μm, 6-25 μm, 7-24 μm, 8-23 μm, 9-22 μm, 10-21 μm, 11-20 μm, 12-19 μm, 13-18 μm, 14-17 μm, 15-16 μm, 3-10 μm, 5-15 μm, 10-20 μm, 15-25 μm, 20-30 μm, etc.

[0097] In some other possible embodiments, the step of preparing the precursor particles includes: after the carbon precursor material is made into particles by crushing and shaping, the particles are mixed with an organic carbon source for granulation, and the granulated product is carbonized to obtain precursor particles. In this case, after the carbon precursor material is crushed and shaped into particles, it is mixed with an organic carbon source for granulation to obtain composite precursor particles, and then the composite precursor particles obtained by the mixed granulation are carbonized to convert the organic carbon source into carbon material by chemical reaction. The precursor particles obtained at this time are secondary particles. The secondary precursor particles obtained by this method can more flexibly and efficiently regulate the size and sphericity of the precursor particles during the granulation process, which is beneficial to improve the specific surface area and microporous structure of the precursor particles.

[0098] In some possible embodiments, the organic carbon source includes asphalt with a softening temperature of 100 to 500°C. The asphalt used in the embodiment of the present application is a dark brown complex mixture composed of hydrocarbons of different molecular weights and their non-metallic derivatives, and is a kind of high viscosity organic liquid carbon source. The asphalt with this softening temperature is used as an organic carbon source, which is solid at room temperature, and is conducive to uniform mixing with the crushed precursor. After the mixed granulation organic carbon source is softened, the crushed particles can be stably bonded together to obtain a mixed granulation product. Exemplarily, the organic carbon source includes a softening temperature of 100 to 200°C, 200 to 300°C, 300 to 400°C, 400 to 500°C, etc.

[0099] In some possible embodiments, the average particle size D50 of the organic carbon source is 0.5-5 μm; in this case, the small particle size of the organic carbon source is conducive to mixing with the crushed particles of the precursor to form composite particles. Exemplarily, the average particle size D50 of the organic carbon source can be 0.5-1 μm, 1-1.5 μm, 1.5-2 μm, 2-2.5 μm, 2.5-3 μm, 3-3.5 μm, 3.5-4 μm, 4-4.5 μm, 4.5-5 μm, etc.

[0100] In some possible embodiments, the mass ratio of particles to organic carbon source is 100:(0.5-5). In this case, after the carbon precursor material is made into particles by crushing and shaping, it is mixed and granulated with the organic carbon source at a mass ratio of 100:(0.5-5). This mass ratio is not only conducive to the mixed granulation to form composite particles of the precursor and the organic carbon source, but also avoids the excessive proportion of organic carbon source in the composite particles of the granulated product, resulting in excessive amorphous carbon content in the secondary precursor particles, which reduces the electrochemical performance of the subsequently prepared graphite negative electrode material. Exemplarily, the mass ratio of particles to organic carbon source can be 100:(0.5-1), 100:(1-2), 100:(2-3), 100:(3-4), 100:(4-5), etc.

[0101] In some possible embodiments, the conditions of the carbonization treatment include: in an inert atmosphere, heating to 600-900°C at a rate of 2-10°C / min and keeping warm for 1-10h. The inert atmosphere includes, but is not limited to, gases such as nitrogen, argon, and helium that do not participate in the reaction of converting the organic carbon source into a carbon material. Under the carbonization conditions, in the secondary precursor particles obtained by mixing and granulating the precursor material and the organic carbon source, the organic carbon source undergoes a pyrolysis reaction at a high temperature to convert the carbon element in the organic carbon source into a structure that forms fixed carbon. Specifically, the organic carbon source undergoes cracking and polymerization reactions under high temperature and oxygen isolation conditions to generate a series of intermediate products and ultimately form a solid carbon material. During the carbonization process, the organic carbon source undergoes different stages, including: in the initial stage, the volatile matter in the organic carbon source is heated and evaporated, leaving a residue containing a high concentration of carbon. As the temperature rises, the organic carbon source begins to undergo a cracking reaction to generate some macromolecular compounds containing a carbon skeleton, i.e., tar. When the temperature rises to a certain extent, the carbon skeleton in the tar will further polymerize to form a compound with a larger molecular weight, i.e., coke. Coke is a solid carbon material with high purity, high density, high strength and high conductivity. In the process of carbonization of organic carbon source, factors such as carbonization temperature, carbonization time, raw material composition, etc. will affect the process and product structure of carbonization reaction. By controlling these factors, carbon materials with different properties and structures can be prepared. Exemplarily, the heating rate of carbonization treatment can be 2-5℃ / min, 5-8℃ / min, 8-10℃ / min, etc., the holding temperature can be 600-700℃, 700-800℃, 800-900℃, etc., and the holding time can be 1-3h, 3-5h, 5-8h, 8-10h, etc.

[0102] In the above step S20, after the precursor particles are graphitized, the graphite particles are screened to obtain a graphite negative electrode material. The embodiment of the present application converts the amorphous or partially ordered carbon material in the precursor particles into a graphite structure with a highly ordered arrangement at high temperature by graphitizing the precursor particles. On the one hand, graphitizing the precursor particles can change the electronic structure in the carbon material of the precursor particles, thereby improving its electrical conductivity. The carbon material after graphitization has higher electrical conductivity and lower resistivity, which is conducive to improving the application performance of the graphite negative electrode material in the battery. On the other hand, since the molecular structure in the carbon material after graphitization is more ordered, its thermal conductivity will also be improved. On the other hand, graphitization can make the structure in the carbon material more compact, thereby improving its mechanical strength and hardness. In addition, the surface of the carbon material after graphitization is smoother and the structure is more stable, which can improve its resistance to chemical corrosion. After graphitization treatment, screening and demagnetization are performed, and the crystallite parameters are screened to meet the following requirements: the average length La along the a-axis direction of the crystallite is ≥ 40 nm, the average thickness Lc along the c-axis direction of the crystallite is ≥ 25 nm, the interlayer spacing d002 is 0.336-0.338 nm, and the number of crystallites contained in a single graphite particle is defined as N = D50. 3 / (La 2 *Lc); wherein D50 is the median particle size of the graphite particles, in μm, and the numerical value of the crystallite number parameter N satisfies 0<N≤0.04. The graphite particles have a stable microcrystalline structure and can improve the expansion and stress distribution uniformity of the negative electrode material during the cycle as a graphite negative electrode material, reduce the consumption rate of active lithium, and thus achieve an ultra-long cycle of the battery system. In addition, the graphite particles have a large crystallite size and a large graphite interlayer spacing, which is conducive to the diffusion of lithium ions in the particles, improves the kinetics of the graphite negative electrode material, and is conducive to the rapid charging of the battery.

[0103] In some possible embodiments, the conditions of the graphitization treatment include: keeping warm for 24 to 72 hours at a temperature of 2400 to 3000°C. Under the graphitization treatment conditions, the precursor particles can be fully graphitized, and the graphitization efficiency is high. Exemplarily, the temperature of the graphitization treatment can be 2400 to 2500°C, 2500 to 2600°C, 2600 to 2700°C, 2700 to 2800°C, 2800 to 2900°C, 2900 to 3000°C, etc., and the graphitization insulation time can be 24 to 36 hours, 36 to 48 hours, 48 ​​to 60 hours, 60 to 72 hours, etc.

[0104] In some possible implementations, the step of graphitization treatment includes: pre-carbonizing the precursor particles at a temperature of 700 to 1200° C. for 2 to 7 days, and then keeping the temperature at a temperature of 2400 to 3000° C. for 24 to 72 hours. In the graphitization process of the embodiment of the present application, the precursor particles are first pre-carbonized to remove the volatile matter in the precursor particles in advance, and then the graphitization treatment is performed, which is conducive to the sample growing into more complete graphite crystals in the subsequent high-temperature graphitization.

[0105] In some specific embodiments, the step of pre-carbonization treatment can be to fill the precursor particles obtained by shaping or granulation into a crucible, send it into a tunnel kiln, and calcine the material in the crucible by igniting natural gas to generate heat. The temperature is in the range of 700 to 1200° C., and the calcination time is 2 to 7 days.

[0106] In some possible embodiments, the step of screening graphite particles includes: screening and demagnetizing the product after graphitization treatment in sequence, and screening graphite particles whose microcrystalline parameters meet the requirements. Among them, screening is used to remove larger particles and debris. Specifically, vibration screening can be used to screen out larger particles and debris to obtain qualified samples. Demagnetization, by controlling magnetic foreign matter through electric current, further purifies the product. Specifically, the screened sample flows into the demagnetization equipment, and the excitation current is passed to control the content of magnetic foreign matter within 5ppm to obtain a demagnetized product. The microcrystalline parameters of the product are further screened to obtain graphite particles whose microcrystalline parameters meet the requirements.

[0107] In some embodiments, after the carbon precursor material is crushed into a particle sample with an average particle size D50 of 1 to 20 μm, a shaping treatment is performed to obtain precursor particles with an average particle size D50 of 1 to 30 μm. After the precursor particles are pre-carbonized at a temperature of 700 to 1200°C for 2 to 7 days, they are graphitized at a temperature of 2400 to 3000°C for 24 to 72 hours. The product after graphitization is vibrated and screened to remove larger particles and debris to obtain qualified samples. The screened sample flows into the demagnetization equipment, and the excitation current is passed to control the content of magnetic foreign matter within 5 ppm to obtain a demagnetization product. The microcrystalline parameters of the product are further screened to obtain graphite particles whose microcrystalline parameters meet the requirements. The graphite particles obtained at this time are single particles.

[0108] In other embodiments, after the carbon precursor material is made into particles by crushing and shaping, the particles are mixed with an organic carbon source including asphalt with a softening temperature of 100 to 500°C for granulation, wherein the average particle size D50 of the organic carbon source is 0.5 to 5 μm, and the mass ratio of the particles to the organic carbon source is 100: (0.5 to 5). The granulated product is heated to 600 to 900°C at a rate of 2 to 10°C / min in an inert atmosphere and kept warm for 1 to 10 hours for carbonization treatment to obtain precursor particles, at which time the precursor particles are secondary particles with an average particle size D50 of 1 to 30 μm. After the precursor particles are pre-carbonized at a temperature of 700 to 1200°C for 2 to 7 days, they are graphitized at a temperature of 2400 to 3000°C for 24 to 72 hours. The product after graphitization treatment is vibrated and screened to remove large particles and impurities, etc., to obtain qualified samples. The screened samples flow into the demagnetization equipment, and the excitation current is passed to control the content of magnetic foreign matter within 5ppm to obtain demagnetized products. The microcrystalline parameters of the product are further screened to obtain graphite particles whose microcrystalline parameters meet the requirements. The graphite particles obtained at this time are secondary particles.

[0109] In some possible embodiments, the number parameter of crystallites contained in a single graphite particle is defined as N=D50 3 / (La 2 *Lc); wherein D50 is the median particle size of the graphite particles, in μm, and the numerical value of the crystallite number parameter N satisfies 0<N≤0.04. Further, the crystallite number parameter 0<N≤0.02. Further, the crystallite number parameter 0.001≤N≤0.01. In this case, it is ensured that the graphite crystallites in the graphite particles have a larger size. The large-sized graphite crystallites provide more deintercalation sites for the insertion and extraction of ions, which is beneficial for ions to enter between the sheets of graphite crystals from the edge embedding sites, improve the ion deintercalation efficiency, and facilitate the rapid transmission of ions. This makes the graphite negative electrode material have better kinetics, reduces the risk of lithium precipitation, and reduces the risk of safety failures such as battery capacity diving and thermal runaway.

[0110] In some possible embodiments, the median particle size D50 of the graphite particles is 5 to 25 μm. Exemplarily, the median particle size D50 of the graphite particles is 7 to 14 μm. The median particle size D50 of the graphite particles ensures the comprehensive electrochemical properties of the graphite negative electrode material, such as cycle stability and rate performance.

[0111] In some possible embodiments, in the graphite particles, the average length along the a-axis direction of the crystallite is 40≤La≤200nm, and the average thickness along the c-axis direction of the crystallite is 25≤Lc≤200nm. The crystallite size La of the graphite crystallites in the 110 crystal plane in the graphite particles is relatively large, and the crystallite thickness Lc in the c-axis direction is also relatively large, thereby ensuring that the graphite crystallites have a relatively large size, and when lithium ions are embedded in the hexagonal mesh layer of the graphite crystal, the expansion uniformity between the crystallites when the ions are embedded in the graphite particles is ensured, the long-cycle stability of the graphite negative electrode is improved, and the influence of the continuous rupture and regeneration and repair of the SEI film on the surface of the graphite negative electrode on the battery cycle life and safety performance is reduced.

[0112] In some possible embodiments, the median particle size D50, particle size D10 and particle size D90 of the graphite particles satisfy (D90-D10) / D50≤1.7. Further, (D90-D10) / D50≤1.5. This indicates that the particle size distribution uniformity of the graphite particles is relatively high, which is beneficial to improving the flatness and thickness uniformity of the film layer prepared by the graphite negative electrode material.

[0113] In some possible embodiments, the specific surface area of ​​the graphite negative electrode material is 0.8 to 2.0 m 2 / g. Furthermore, the specific surface area is 0.9 to 1.5 m 2 / g. The size range of the specific surface area of ​​the graphite negative electrode material in the embodiment of the present application balances the relationship between the reaction rate, capacity and mechanical stability of the graphite negative electrode material to achieve optimal electrochemical performance and safety performance.

[0114] In a third aspect, an embodiment of the present application provides a battery pole piece, which contains the above-mentioned graphite negative electrode material or the graphite negative electrode material prepared by the above-mentioned method.

[0115] The battery electrode provided in the third aspect of the embodiment of the present application comprises the above-mentioned graphite negative electrode material, wherein the graphite negative electrode material comprises graphite particles having an average length La ≥ 40 nm along the a-axis direction of the microcrystal, an average thickness Lc ≥ 25 nm along the c-axis direction of the microcrystal, and an interlayer spacing d002 of 0.336 to 0.338 nm, and the number parameter of the microcrystals contained in a single graphite particle is defined as N = D50 3 / (La 2 *Lc)≤0.04. Therefore, the microcrystalline structure of the graphite negative electrode material is stable. When applied to the battery pole piece, it can improve the expansion and stress distribution uniformity of the battery pole piece during the cycle, reduce the consumption rate of active lithium, and thus achieve an ultra-long cycle of the battery system. In addition, the graphite negative electrode material has a large microcrystalline size and a large graphite layer spacing, which is conducive to the diffusion of lithium ions in the particles, improves the dynamics of the battery pole piece, and is conducive to the rapid charging of the battery.

[0116] In some possible implementations, the battery electrode is a negative electrode, which includes a negative electrode collector and a negative electrode material layer coated on the surface of the negative electrode collector. The negative electrode material layer includes the graphite negative electrode material of the above embodiment and may also include a certain amount of binder, conductive agent and other components.

[0117] In some possible implementations, the negative electrode active material may include, in addition to the above-mentioned graphite negative electrode material, silicon-based negative electrode materials such as silicon alone, compounds formed by silicon and non-metals, compounds formed by silicon and metals, or lithium titanate, etc. This is only for illustrative purposes and is not specifically limited here.

[0118] In some possible implementations, the negative electrode current collector may be a metal foil, such as copper foil, gold foil, platinum foil, etc. This is only for illustrative purposes and is not specifically limited here.

[0119] In some possible implementations, the negative electrode binder may be typically but not limited to sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber (SBR), polyacrylic acid (PAA), lithium polyacrylate (LiPAA), etc. This is only for illustrative purposes and is not specifically limited here.

[0120] In some possible implementations, the negative electrode conductive agent may be typically but not limited to amorphous carbon, carbon nanotubes, carbon fibers, graphene, etc. This is only for illustrative purposes and is not specifically limited herein.

[0121] In some possible implementations, the preparation of the negative electrode sheet includes the steps of: mixing the negative electrode active material with a conductive agent such as conductive carbon black, a binder such as carboxymethyl cellulose and styrene-butadiene rubber, and a solvent such as water in a mass ratio of (80-99):(1-5):(2-10):100 to form a negative electrode mixed slurry, vacuum degassing, discharging, coating on a coating machine, and obtaining a negative electrode sheet after rolling, slitting, and die-cutting.

[0122] In some possible implementations, the negative electrode sheet of the battery of the present application is combined with lithium metal to form a button cell, and the first lithium insertion capacity in the voltage range of 0.005 to 2V is 355 to 74 mAh / g, the reversible lithium desorption capacity is 330 to 348 mAh / g, and the first coulombic efficiency is 90% to 95%.

[0123] In a fourth aspect, an embodiment of the present application provides a secondary battery, wherein the secondary battery comprises the above-mentioned battery electrode.

[0124] The secondary battery provided in the fourth aspect of the embodiment of the present application comprises the above-mentioned battery pole piece, which comprises a graphite negative electrode material with a stable microcrystalline structure, a large microcrystalline size and a large graphite layer spacing, so that the battery pole piece has excellent kinetic performance and long-cycle stability, thereby improving the electrochemical properties of the secondary battery such as the rate performance and cycle performance, reducing the risk of lithium plating, reducing the impact of continuous rupture and regeneration and repair of the SEI film on the electrode surface on the battery cycle life and safety performance, and reducing the risk of safety failures such as battery capacity diving and thermal runaway.

[0125] In some possible implementations, lithium-ion batteries are described as typical systems or scenarios of secondary batteries. The core components of lithium-ion batteries are mainly positive electrodes, negative electrodes, separators, and electrolytes, and the battery plates contained in secondary batteries are negative electrode plates. During charging, lithium ions are released from the lattice of the positive electrode material containing lithium, migrate through the separator in the electrolyte to the surface of the negative electrode graphite, and then desolvate. They diffuse through ions in the SEI on the surface of the negative electrode to reach the graphite negative electrode, complete the charge transfer reaction, and the electrons are reduced and embedded in the graphite layer. During discharge, the reverse process occurs, and the lithium ions are re-embedded from the negative electrode through the electrolyte and separator into the lattice of the positive electrode material. During the charge and discharge cycle, the intrinsic expansion of the negative electrode not only causes the surface SEI to continue to grow and repair the consumption of active lithium, but also causes uneven stress distribution inside the negative electrode particles, resulting in damage to the particle structure. Both of these will cause the battery capacity to decay. The lithium battery with graphite negative electrode material having long cycle stability and excellent kinetic performance adopted in the embodiment of the present application has the characteristics of long cycle life. The system matched with lithium iron phosphate positive electrode can achieve more than 10,000 cycles, which is suitable for various energy storage scenarios. It can also be used in fields such as electric vehicles.

[0126] The present application does not specifically limit the positive electrode, electrolyte, separator, etc. in the secondary battery of the embodiment, and can be applied to any battery system.

[0127] In some possible implementations, the positive electrode in the secondary battery includes a positive electrode current collector and a positive electrode material layer coated on the surface of the positive electrode current collector. In addition to the positive electrode active material, the positive electrode material layer may also include a certain amount of binder, conductive agent and other components.

[0128] In some possible implementations, the positive electrode active material in the secondary battery includes metal oxides, such as lithium cobalt oxide, lithium nickel oxide, nickel cobalt manganese ternary materials, lithium nickel cobalt aluminum oxide, lithium-rich manganese-based materials, lithium manganate, lithium nickel manganate, ferroferric oxide, lithium vanadate, etc. Phosphates, silicates, sulfates, borates, titanates and other polyanion salts, such as lithium iron phosphate, lithium manganese phosphate, lithium iron manganese phosphate, lithium vanadium phosphate, lithium vanadium phosphate, lithium cobalt phosphate, lithium nickel phosphate, lithium iron silicate, lithium fluorosulfate, lithium iron borate, lithium iron titanate, etc. And fluorides, sulfides, selenides and other types, such as iron trifluoride, cobalt trifluoride, nickel trifluoride (NiF3), titanium disulfide, iron disulfide, molybdenum disulfide, niobium triselenide, etc.

[0129] In some possible implementations, the positive electrode current collector may be a metal foil, such as aluminum foil, gold foil, platinum foil, etc. This is only for illustrative purposes and is not specifically limited here.

[0130] In some possible implementations, the positive electrode binder may be typically but not limited to polyvinylidene fluoride (PVDF), acrylonitrile multipolymer, polyacrylic acid, hydroxypropyl methylcellulose, etc. This is only for illustrative purposes and is not specifically limited here.

[0131] In some possible implementations, the positive electrode conductive agent may be typically but not limited to amorphous carbon, carbon nanotubes, carbon fibers, graphene, etc. This is only for illustrative purposes and is not specifically limited herein.

[0132] In some possible implementations, the preparation of the positive electrode includes the steps of: mixing the positive electrode active material with a conductive agent such as conductive carbon black, a binder such as polyvinylidene fluoride, and a solvent such as N-methylpyrrolidone in a mass ratio of (80-99):(1-5):(2-10):100 to form a positive electrode mixed slurry, vacuum degassing, discharging, coating on a coating machine, and obtaining the positive electrode 10 after rolling, slitting, and die-cutting.

[0133] In some possible implementations, in a secondary battery, the separator can block the passage of electrons but allow the passage of ions. Exemplary separators include, but are not limited to, single-layer polypropylene (PP), single-layer polyethylene (PE), double-layer PP / PE, double-layer PP / PP, triple-layer PP / PE / PP, and ceramic-coated PE.

[0134] In some possible implementations, the electrolyte in the secondary battery includes at least one soluble metal salt.

[0135] In some possible implementations, the secondary battery types include lithium-ion batteries, as well as new batteries such as sodium-ion batteries and lithium-air batteries.

[0136] In some possible implementations, the secondary battery is in the form of at least one of a battery cell, a battery module, and a battery pack.

[0137] In some possible implementations, the battery cell types include lithium ion batteries, and new batteries such as sodium ion batteries, lithium air batteries, and lithium metal batteries. The present application embodiment has no particular limitation on the shape of the battery cell, which may be cylindrical, square, or any other shape.

[0138] In some possible implementations, the battery cells according to the embodiments of the present application may be assembled into a battery module. The battery module may contain multiple battery cells, and the specific number may be adjusted according to the application and capacity of the battery module.

[0139] In a possible implementation, the battery cells and / or battery modules of the embodiment of the present application may also be assembled into a battery pack, and the number of battery cells or battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0140] In a fifth aspect, an embodiment of the present application provides an energy storage device, which includes the secondary battery mentioned above.

[0141] The energy storage device provided in the fifth aspect of the embodiment of the present application improves the comprehensive performance of the energy storage device, such as stability and safety, by including the secondary battery with the above-mentioned characteristics of good long-cycle stability, good rate performance, and high safety performance. Therefore, the energy storage device of the embodiment of the present application has good cycle performance and long service life.

[0142] The energy storage device of the embodiment of the present application includes an energy storage unit, and of course may also include other auxiliary components or necessary components. Among them, the energy storage unit contains the secondary battery of the embodiment of the above text application. The secondary battery contained in the energy storage unit may be one or more. When there are multiple secondary batteries, multiple secondary batteries can form a battery module or a battery pack. Since the energy storage device of the embodiment of the present application contains the above-mentioned secondary battery of the embodiment of the present application, the energy storage device has good cycle performance, long service life, and further high energy density.

[0143] In a sixth aspect, an embodiment of the present application provides an electrical device, which includes the secondary battery described above.

[0144] The electric device provided in the sixth aspect of the embodiment of the present application comprises a secondary battery having the above-mentioned characteristics of good long cycle stability, good rate performance, high safety performance, etc., thereby improving the use stability and safety of the electric device.

[0145] In a possible implementation, the electrical equipment may select a secondary battery in the form of a battery cell, a battery module or a battery pack in the above-mentioned embodiment according to its usage requirements.

[0146] In one possible implementation, the electrical device may be, but is not limited to, a mobile device, such as a mobile phone, a laptop computer, etc., or an electric vehicle, such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc., or an electric train, a ship and a satellite, an energy storage system, etc.

[0147] In some specific embodiments, the electric device may be a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, etc. In order to meet the requirements of such electric devices for high power and high energy density of batteries, the above-mentioned battery pack or battery module may be used.

[0148] In some specific implementations, the electrical device may also be a recorder, a radio, an electronic learning machine, a mobile phone, a tablet computer, a laptop computer, etc. Such electrical devices are usually required to be light and thin, and the battery cell in the above embodiment may be used as a power source.

[0149] Example

[0150] The following is explained in conjunction with specific embodiments. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer of the reagents or instruments is not indicated, they are all conventional products that can be obtained commercially.

[0151] Example 1

[0152] The present application embodiment provides a graphite negative electrode material, the preparation of which includes the following steps:

[0153] ① The calcined petroleum coke raw material C1 (fixed carbon content not less than 60%) was initially crushed by a coarse crusher and then sent to a mechanical mill for further pulverization to obtain a particle sample with an average particle size D50 of 11±0.5μm.

[0154] ② The crushed raw material particle sample is put into the particle shaping equipment, and the particle sample is subjected to shaping operations such as de-edging to obtain a shaped sample with an average particle size D50 of 11±1μm.

[0155] ③Put the shaped sample into a graphite crucible and put it into the Acheson graphitization furnace for high-temperature graphitization. The high-temperature graphitization treatment temperature is 2800℃ and the heat preservation time is 48h. Then cool it down to room temperature for 30 days to obtain the graphitized sample.

[0156] ④ Add the graphitized sample to the vibrating screen to screen out larger particles and impurities, take the sample under the screen for subsequent demagnetization operation, and screen the products whose microcrystalline parameters meet the requirements, as shown in Table 1 below, and finally obtain the graphite negative electrode material 1.

[0157] Example 2

[0158] The present application embodiment provides a graphite negative electrode material, the preparation of which includes the following steps:

[0159] ① The calcined petroleum coke raw material C2 (fixed carbon content not less than 60%) is initially crushed by a coarse crusher and then sent to a mechanical mill for further pulverization to obtain a particle sample with an average particle size D50 of 8±0.5μm.

[0160] ② The crushed raw material particle sample is put into the particle shaping equipment, and the particle sample is subjected to shaping operations such as de-edging to obtain a shaped sample with an average particle size D50 of 8±1μm.

[0161] ③Put the shaped sample into a graphite crucible and put it into an inner furnace for high-temperature graphitization. The high-temperature graphitization treatment temperature is 2850℃ and the holding time is 55h. Then cool it down to room temperature for 10 days to obtain a graphitized sample.

[0162] ④ Add the graphitized sample to the vibrating screen to screen out larger particles and impurities, take the sample under the screen for subsequent demagnetization operation, and screen the products whose microcrystalline parameters meet the requirements, as shown in Table 1 below, and finally obtain the graphite negative electrode material 2.

[0163] Example 3

[0164] The present application embodiment provides a graphite negative electrode material, the preparation of which includes the following steps:

[0165] ① The asphalt coke raw material C3 (fixed carbon content not less than 60%) is initially crushed by a coarse crusher and then sent to a mechanical mill for further pulverization to obtain a particle sample with an average particle size D50 of 11.0±0.5μm.

[0166] ② The crushed raw material particle sample is put into the particle shaping equipment, and the particle sample is subjected to shaping operations such as de-edging to obtain a shaped sample with an average particle size D50 of 11.0±1μm.

[0167] ③ The shaped samples were placed in a stainless steel crucible and sent into a kiln for pre-carbonization. The samples were heated by igniting natural gas and calcined at 1000°C for 48 hours, then cooled to obtain pre-carbonized products.

[0168] ④Put the pre-carbonized product into a graphite crucible and perform high-temperature graphitization in an Acheson graphitization furnace. The high-temperature graphitization treatment temperature is 2800°C and the heat preservation time is 48 hours. Then cool down to room temperature for 30 days to obtain a graphitized sample.

[0169] ⑤ Add the graphitized sample to the vibrating screen to screen out larger particles and impurities, take the sample under the screen for subsequent demagnetization operation, and screen the products whose microcrystalline parameters meet the requirements, as shown in Table 1 below, and finally obtain the graphite negative electrode material 3.

[0170] Example 4

[0171] The present application embodiment provides a graphite negative electrode material, the preparation of which includes the following steps:

[0172] ① The asphalt coke raw material C4 (fixed carbon content not less than 60%) is initially crushed by a coarse crusher and then sent to a mechanical mill for further pulverization to obtain a particle sample with an average particle size D50 of 9.0±0.5μm.

[0173] ② The crushed raw material particle sample is put into the particle shaping equipment, and the particle sample is subjected to shaping operations such as de-edging to obtain a shaped sample with an average particle size D50 of 9.0±1μm.

[0174] ③ The shaped sample was mixed with asphalt material with a softening temperature of 250°C in a mass ratio of 100:1.5, and sent into a granulation reactor. The granulation was carried out under heating in an inert atmosphere with stirring. The temperature of the reactor was maintained at 700°C. After reacting for 8 hours, the sample was cooled to obtain a granulated sample.

[0175] ④ The granulated samples were placed in a box furnace for high-temperature graphitization. The treatment temperature for high-temperature graphitization was 2700°C and the holding time was 48 hours. The temperature was then lowered to room temperature to obtain graphitized samples.

[0176] ⑤ Add the graphitized sample into a blender to break it up to prevent large pieces from agglomerating, and obtain secondary particle artificial graphite with a D50 of 16.5±1μm.

[0177] ⑥ Add the broken graphitized sample to the vibrating screen to screen out larger particles and debris, take the sample under the screen for subsequent demagnetization operation, and screen the products whose microcrystalline parameters meet the requirements, as shown in Table 1 below, and finally obtain the graphite negative electrode material 4.

[0178] Comparative Example 1

[0179] This comparative example provides a graphite material, the preparation of which includes the steps of:

[0180] ① After the petroleum coke raw material D1 is initially crushed by a coarse crusher, it is sent to a mechanical mill for further pulverization to obtain a particle sample with an average particle size D50 of 12±0.5μm.

[0181] ② The crushed graphite sample is placed in a particle shaping device to perform shaping operations such as de-edging the graphite particles to obtain a shaped sample with an average particle size D50 of 12±1 μm.

[0182] ③Put the shaped sample into a graphite crucible and put it into the Acheson graphitization furnace for high-temperature graphitization. The high-temperature graphitization treatment temperature is 2900℃ and the holding time is 60h. Then cool it down to room temperature for 35 days to obtain a graphitized sample.

[0183] ④ Add the graphitized sample to the vibrating screen to screen out larger particles and impurities, take the sample under the screen for subsequent demagnetization operation, and obtain graphite material D1, whose crystallite parameters are shown in Table 1 below.

[0184] Comparative Example 2

[0185] This comparative example provides a graphite material, the preparation of which includes the steps of:

[0186] ① After the asphalt coke raw material D2 is initially crushed by a coarse crusher, it is sent to a mechanical mill for further pulverization to obtain a particle sample with an average particle size D50 of 8.0±0.5μm.

[0187] ② The crushed graphite sample is placed in a particle shaping device to perform shaping operations such as de-edging the graphite particles to obtain a shaped sample with an average particle size D50 of 8.0±1μm.

[0188] ③ The shaped sample was mixed with asphalt material with a softening temperature of 250°C in a mass ratio of 100:1.5, and sent into a granulation reactor. The granulation was carried out under heating in an inert atmosphere with stirring. The temperature of the reactor was maintained at 700°C. After reacting for 8 hours, the sample was cooled to obtain a granulated sample.

[0189] ④ The granulated samples were placed in a box furnace for high-temperature graphitization. The treatment temperature for high-temperature graphitization was 2800°C and the holding time was 48 hours. The temperature was then lowered to room temperature to obtain graphitized samples.

[0190] ⑤ Add the graphitized sample into a blender to break it up to prevent large pieces from agglomerating, and obtain secondary particle artificial graphite with a D50 of 16.5±1μm.

[0191] ⑥ Add the broken graphitized sample to the vibrating screen to screen out larger particles and impurities, take the sample under the screen for subsequent demagnetization operation, and obtain graphite material D2, whose crystallite parameters are shown in Table 1 below.

[0192] In order to verify the progress of the embodiments of the present application, the above embodiments and comparative examples were subjected to the following physicochemical performance and electrochemical tests:

[0193] 1. XRD test to verify the crystallite parameters of the sample: The graphite negative electrode material prepared in the above embodiments and the graphite material powder samples prepared in the comparative example are placed in the XRD special sample stage, flattened with a cover glass, and loaded into the test instrument. The XRD test uses Cu Kα radiation, the test range is 2θ=10~90°, and the scanning speed is 2° / min. After obtaining the XRD spectrum of each sample, according to the Scherrer formula (D=kλ / βcosθ, where D is the grain size, i.e. La, k is the shape factor (generally 0.9~1.0), λ is the wavelength of the incident light, β is the peak width, and θ is the diffraction angle), the average crystallite size La(110) of the prepared graphite sample in the single sheet basal plane and the average crystallite size Lc(002) in the c-axis direction are calculated, and the peak position and half-peak width of the 110 crystal plane and the 002 crystal plane are used for calculation, respectively, in nm.

[0194] 2. XRD test verifies the graphitization degree and d002 of the sample: refer to the determination method of interlayer spacing d002 in the national standard GB / T24533-2019. During the XRD test, a high-purity single crystal Si sample is mixed as an internal standard to calculate the diffraction peak position of the (002) crystal plane of the graphite sample (half-peak width calibration is required), and then the Bragg equation (nλ=2dsinθ, where n is the diffraction order, λ is the wavelength of the incident light, d is the interplane spacing of the crystal, and θ is the angle between the incident light and the crystal plane) is used to calculate the interplane spacing d002 of the prepared graphite sample, in nm. The degree of graphitization is calculated as G=(0.3440-d002) / 0.0086*100%.

[0195] 3. Particle size distribution test: Referring to the national standard GB / T 24533-2019 lithium ion battery graphite negative electrode material-determination method of particle size distribution, the graphite samples prepared in each embodiment and comparative example were dispersed in a pure water solvent, and the graphite dispersed in the pure water solvent was tested by laser particle size using a Malvern MS-3000 instrument to obtain the Dv10, Dv50, and Dv90 information of each sample.

[0196] 4. Specific surface area test: The NOVA-Touch specific surface area tester was used to perform nitrogen adsorption and desorption test (BET method) with high-purity N2 as the adsorbent to obtain the BET specific surface area of ​​each sample.

[0197] 5. Electrochemical test: The graphite materials prepared in the examples and comparative examples were mixed with CMC-SBR dispersant and adhesive to form an aqueous solution, and the slurry was coated on the copper foil current collector to obtain the graphite negative electrode sheet, and then rolled. The sheet was punched into a disc with a diameter of 16 mm, and the coating weight of a single film was controlled to be 20 mg, and the compaction density was 1.55 g / cm 3The obtained negative electrode sheet and lithium metal sheet were assembled into a CR2430 button cell, and a small current discharge and charge were performed between 0.005V and 2V on a charge and discharge device. The reversible capacity and first efficiency of the graphite negative electrode material were obtained.

[0198] The test results of the above test items are shown in Table 1 below:

[0199] Table 1

[0200]

[0201] It can be seen from the test data in Table 1 that the graphite negative electrode materials prepared in Examples 1 to 4 of the present application all meet the graphite crystallite size La ≥ 40nm, Lc ≥ 25nm. The interlayer spacing d002 in the c-axis direction is between 0.336 and 0.338nm, and the crystallite number parameter N = D50 3 / (La 2 *Lc) are all less than or equal to 0.04. It shows that the graphite negative electrode material prepared in the embodiment of the present application has a small number of crystallites per unit volume, a relatively large crystallite size, a large interlayer spacing, and a reduced degree of graphitization, which is beneficial to improving the long-cycle stability and kinetic performance of the graphite negative electrode material. Comparative Examples 1 and 2 use conventional petroleum coke raw materials as precursors to prepare single-particle or secondary-particle graphite negative electrode materials, and the crystallite parameters of the graphite particles are not screened. It can be seen from the test that the crystallite parameters of the graphite particles are small, the degree of graphitization is high, and the crystallite number parameter is high, indicating that the number of crystallites per unit volume is large and the crystallite size is small, which is not conducive to providing the long-cycle stability and kinetic performance of the graphite negative electrode material.

[0202] 6. Cycle performance test: The graphite negative electrode materials prepared in each embodiment and the graphite materials prepared in the comparative example were assembled into lithium iron phosphate LFP-graphite soft-pack batteries, and subjected to 0.5C / 0.5C cycling at 25°C and 1C / 1C accelerated cycling at a high temperature of 55°C.

[0203] The preparation steps of lithium iron phosphate LFP-graphite soft pack battery are as follows:

[0204] ① Preparation of positive electrode sheet: Weigh 2% polyvinylidene fluoride (PVDF), 2% conductive agent Super P and 96% lithium iron phosphate positive electrode active material by weight, add them into N-methylpyrrolidone (NMP) in sequence, stir and mix them evenly, apply the slurry on the aluminum foil current collector, dry, cold press and cut to obtain positive electrode sheet.

[0205] ② Preparation of negative electrode sheet: Weigh 1.5% sodium carboxymethyl cellulose (CMC), 2.5% styrene-butadiene rubber (SBR), 1% Super P and 95% of the graphite negative electrode material prepared in each embodiment or comparative example as negative electrode active materials, add them into deionized water in sequence, stir and mix them evenly, coat the slurry on a copper foil current collector, dry, cold press and cut to obtain negative electrode sheets.

[0206] ③ Preparation of electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) are mixed in a mass ratio of EC:EMC:DMC=30:30:40, and then lithium hexafluorophosphate (LiPF6) is added to the resulting mixture to a molar concentration of 1 mol / L to obtain an electrolyte.

[0207] ④Battery assembly: The positive electrode sheet, negative electrode sheet and commercial PE separator prepared above are made into battery cells, packaged with polymer, and infused with the electrolyte prepared above. After infiltration, formation and capacity separation, a 4Ah LFP-graphite soft-pack battery cell is obtained.

[0208] The capacity retention rate of the LFP-graphite soft-pack battery cell prepared by the graphite materials of the above embodiments and comparative examples after 500 cycles of 0.5C / 0.5C at 25°C and 1000 cycles of 1C / 1C accelerated cycle at high temperature of 55°C is shown in Table 2 below.

[0209] Table 2

[0210]

[0211] It can be seen from the test data in Table 2 that compared with the lithium-ion batteries prepared in the comparative examples, the lithium-ion batteries prepared by the graphite negative electrode materials provided in the embodiments of the present application have a small number of crystallites per unit volume, a relatively large crystallite size, and a large interlayer spacing. In the process of lithium ion embedding into the hexagonal graphite mesh layer, the kinetics can be faster, ensuring good expansion uniformity between crystallites when lithium is embedded inside the particles, and slow consumption of active lithium. Therefore, the lithium-ion batteries prepared by the single-particle graphite negative electrode materials of Examples 1 to 3 of the present application and the secondary-particle graphite negative electrode materials of Example 4, whether 0.5C / 0.5C at 25°C or 1C / 1C at 55°C, have a capacity retention rate at the same number of cycles that is much higher than that of the lithium-ion batteries prepared by the graphite materials of Comparative Examples 1 and 2. In addition, the lithium-ion batteries prepared by the single-particle graphite negative electrode materials of Examples 1 to 3 of the present application exhibit better cycle stability.

[0212] 7. In order to verify the dynamics of the graphite negative electrode material of the present application, the graphite negative electrode materials prepared in each embodiment and the graphite materials prepared in the comparative example were assembled into a soft-pack battery cell of lithium iron phosphate LFP-graphite, and the experiments of charging and disassembly to judge lithium precipitation at 1C, 1.5C, and 2C at 25°C were carried out. Among them, the preparation method of the soft-pack battery cell of lithium iron phosphate LFP-graphite is the same as that of test 6.

[0213] The LFP-graphite soft-pack batteries prepared by the above examples and comparative examples were charged and disassembled at 1C, 1.5C and 2C at 25°C to determine lithium deposition. The test results are shown in Table 3 below.

[0214] Table 3

[0215] Serial number Sample name 25℃1C 25℃1.5C 25℃2C Example 1 Single particle graphite negative electrode material 1 No lithium precipitation No lithium precipitation No lithium precipitation Example 2 Single particle graphite negative electrode material 2 No lithium precipitation No lithium precipitation No lithium precipitation Example 3 Single particle graphite negative electrode material 3 No lithium precipitation No lithium precipitation No lithium precipitation Example 4 Secondary particle graphite negative electrode material 4 No lithium precipitation No lithium precipitation No lithium precipitation Comparative Example 1 Single Particle Graphite Material D1 No lithium precipitation Lithium Separation Lithium Separation Comparative Example 2 Secondary Particle Graphite Material D2 No lithium precipitation No lithium precipitation Lithium Separation

[0216] It can be seen from the test data in Table 3 that the lithium-ion batteries prepared from the graphite negative electrode materials of Examples 1 to 4 of the present application meet the requirements of no lithium precipitation during 2C charging and disassembly at room temperature, indicating that the graphite negative electrode materials prepared in the embodiments of the present application have good kinetic performance, reduce the risk of lithium precipitation, and reduce the risk of safety failures such as battery capacity diving and thermal runaway. It is also beneficial to improve the electrochemical properties of the applied battery, such as rate performance and cycle performance. However, the lithium-ion battery prepared from the single-particle graphite material of Comparative Example 1 does not precipitate lithium at 1C, but precipitates lithium at 1.5C, and the kinetics are poor; the lithium-ion battery prepared from the secondary particle graphite material of Comparative Example 2 meets the requirements of no lithium precipitation at 1.5C, but precipitates lithium at 2C, and the kinetics are also significantly lower than the battery used for the graphite negative electrode material of the embodiments of the present application.

[0217] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those of ordinary skill in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in each embodiment can be combined in any way. The scope of protection of the present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims. Therefore, the scope of protection of the present application shall be based on the scope of protection of the claims.

Claims

1. A graphite negative electrode material, characterized in that: The graphite negative electrode material includes graphite particles with an average length La≥40nm along the a-axis direction of the microcrystal, an average thickness Lc≥25nm along the c-axis direction of the microcrystal, and an interlayer spacing d002 of 0.336-0.338nm. The number parameter of microcrystals contained in a single graphite particle is defined as N=D50. 3 / (La 2 *Lc); wherein D50 is the median particle size of the graphite particles, in μm, and the numerical value of the crystallite number parameter N satisfies 0<N≤0.

04.

2. The graphite negative electrode material according to claim 1, characterized in that The crystallite number parameter 0<N≤0.

02.

3. The graphite negative electrode material according to claim 2, characterized in that The crystallite number parameter is 0.001≤N≤0.

01.

4. The graphite negative electrode material according to claim 1, characterized in that The La is ≤ 200nm, and the Lc is ≤ 200nm.

5. The graphite negative electrode material according to claim 1, characterized in that The median particle size D50 of the graphite particles is 5 to 25 μm.

6. The graphite negative electrode material according to claim 5, characterized in that The median particle size D50 of the graphite particles is 7 to 14 μm.

7. The graphite negative electrode material according to any one of claims 1 to 6, characterized in that: The median particle size D50, the particle size D10 and the particle size D90 of the graphite particles satisfy (D90-D10) / D50≤1.

7.

8. The graphite negative electrode material according to claim 7, characterized in that The median particle size D50, the particle size D10 and the particle size D90 of the graphite particles satisfy (D90-D10) / D50≤1.

5.

9. The graphite negative electrode material according to claim 1 or 8, characterized in that The specific surface area of ​​the graphite negative electrode material is 0.8 to 2.0 m 2 / g.

10. The graphite negative electrode material according to claim 9, characterized in that The specific surface area of ​​the graphite negative electrode material is 0.9 to 1.5 m 2 / g.

11. The graphite negative electrode material according to claim 1 or 10, characterized in that: The graphite particles are single particles or secondary particles.

12. A method for preparing a graphite negative electrode material, characterized in that: The following steps are involved: forming a carbon precursor material into precursor particles; After the precursor particles are graphitized, the graphite particles are screened to obtain a graphite negative electrode material; in the graphite particles, the average length La along the a-axis direction of the microcrystal is ≥40nm, the average thickness Lc along the c-axis direction of the microcrystal is ≥25nm, the interlayer spacing d002 is 0.336-0.338nm, and the number parameter of microcrystals contained in a single graphite particle is defined as N=D50 3 / (La 2 *Lc); wherein D50 is the median particle size of the graphite particles, in μm, and the numerical value of the crystallite number parameter N satisfies 0<N≤0.

04.

13. The method for preparing a graphite negative electrode material according to claim 12, characterized in that: The fixed carbon content in the carbon precursor material is not less than 60%; and / or, The carbon precursor material includes at least one of calcined petroleum coke, calcined petroleum coke, coal tar coke and anthracite.

14. The method for preparing a graphite negative electrode material according to claim 12, characterized in that: The step of preparing the precursor particles comprises: crushing the carbon precursor material into particle samples with an average particle size D50 of 1 to 20 μm, and then performing shaping treatment to obtain the precursor particles with an average particle size D50 of 1 to 30 μm.

15. The method for preparing a graphite negative electrode material according to claim 12, characterized in that: The step of preparing the precursor particles comprises: preparing the carbon precursor material into particles by crushing and shaping, mixing the particles with an organic carbon source for granulation, and carbonizing the granulated product to obtain the precursor particles.

16. The method for preparing a graphite negative electrode material according to claim 15, characterized in that: The organic carbon source includes asphalt having a softening temperature of 100 to 500° C.; and / or, The average particle size D50 of the organic carbon source is 0.5 to 5 μm; and / or, The mass ratio of the particles to the organic carbon source is 100:(0.5-5).

17. The method for preparing a graphite negative electrode material according to claim 15, characterized in that: The carbonization treatment conditions include: in an inert atmosphere, heating to 600-900° C. at a rate of 2-10° C. / min and keeping the temperature for 1-10 hours.

18. The method for preparing a graphite negative electrode material according to any one of claims 12 to 17, characterized in that: The graphitization treatment conditions include: keeping the temperature at 2400-3000° C. for 24-72 hours.

19. The method for preparing a graphite negative electrode material according to claim 18, characterized in that: The graphitization treatment step includes: pre-carbonizing the precursor particles at a temperature of 700-1200° C. for 2-7 days, and then maintaining the temperature at a temperature of 2400-3000° C. for 24-72 hours.

20. The method for preparing a graphite negative electrode material according to claim 12 or 19, characterized in that: The step of screening graphite particles comprises: sequentially screening and demagnetizing the product after the graphitization treatment, and screening the graphite particles whose microcrystalline parameters meet the requirements.

21. A battery pole piece, characterized in that: The battery pole piece contains the graphite negative electrode material as described in any one of claims 1 to 11 or the graphite negative electrode material prepared by the method as described in any one of claims 12 to 20.

22. A secondary battery, characterized in that: The secondary battery comprises the battery electrode as claimed in claim 21.

23. An energy storage device, characterized in that: The energy storage device includes the secondary battery as claimed in claim 22.

24. An electrical device, characterized in that: The electrical device comprises the secondary battery as claimed in claim 22.

Citation Information

Cited By

  • Graphite-based negative electrode material and preparation method and application thereof

    CN119812319A

  • Graphite-based negative electrode material and preparation method and application thereof

    CN119812319B

  • Lithium ion secondary battery, carbon material, preparation method of lithium ion secondary battery and carbon material, and electric device

    CN122091491A

  • Graphite and preparation method thereof, negative electrode plate, secondary battery, and energy storage device

    WO2026153408A1